EPIDERMAL CHARACTERISTICS AND EPIDERMAL DERIVATIVES OF THE LEAVES OF Ipomoea pes-caprae (L.) R. Br. IN THE DEPOK BEACH AREA OF YOGYAKARTA - Zuchrotus Salamah; Hadi Sasongko; Lina Radhita Vebriyani (BIOEDUKASI, 2022)
Depok Beach is a sandy beach that has limited vegetation because of strong winds, poor microclimate, and low availability of nutrients. One of the plants that can adapt to these extreme conditions is Ipomoea pes-caprae (L.) R. Br. One form of its adaptation to extreme environments is thickening the leaves. Other forms of adaptation can also be studied through the characteristics of the epidermis and the epidermal derivatives of the leaves, as the focus of this study. This type of research is exploratory research, including sampling, plant identification, leaf preparation using the leaf clearing method, and observing microscopic preparations. The data analysis used is descriptive quantitative. The data obtained include the characteristics of the epidermis and its derivatives in the form of stomata and trichomes. The results showed the average number of epidermal cells in the adaxial part of the leaves higher, that is equal to 54.05 ± 2.31 / 0.06 mm2. Stomata are parasitic and amphistomatic. The size of the stomata and the width of the stomatal pore on the adaxial surface of the leaf is smaller but has a higher average density, which is 5.80 ± 1.15 / 0.06 mm2. The trichomes found were of the glandular type.